Preparation method of flame-retardant thin spraying material for organic-inorganic composite mine
The flame-retardant thin injector materials for organic-inorganic composite minerals were prepared by seed emulsion polymerization method, and the flame-retardant monomer and inorganic materials with DOPO structure were used to form a dual crosslinking network structure, which solved the flame-retardant performance, toughness and cost of existing materials. The defects in the aspects achieve high-performance flame retardant and mechanical properties.
Patent Information
- Application Number
- CN202411526651.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-11
AI Technical Summary
The existing thin-layer spraying materials for minerals have defects in flame retardant performance, toughness and cost, and it is difficult to meet the support needs of the complex geological environment underground in coal mines.
Acrylate copolymerization emulsions were prepared by seed emulsion polymerization method. By introducing flame retardant monomers and inorganic materials with structures containing DOPO, a physical/chemical double crosslinked organic-inorganic composite network structure was formed to improve the flame retardant and mechanical properties of the material.
It achieves high-performance flame retardant and mechanical properties, which is suitable for the support needs of complex geological environments underground in coal mines. At the same time, the process is simple, green and environmentally friendly, reducing costs.
Smart Images

Figure CN119409448A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a method for preparing an organic-inorganic composite flame-retardant thin spray material for mining. Background Art
[0002] Coal mining production faces complex geological environmental conditions. The coal-bearing strata in underground tunnels are mainly composed of sandstone, coal rock, shale and other rocks with poor mechanical properties. Such rocks are easily weathered and softened after absorbing water, and even become muddy, expand and disintegrate. Due to the humid environment and widespread water leakage in coal mines, the metal anchor mesh support system is prone to rust, resulting in a reduction in its restraint on the surrounding rock. Therefore, the traditional anchor mesh support method faces severe challenges.
[0003] Thin layer spraying for mining is a technology that uses spraying technology to protect the surface. The sprayed thin layer is formed on the surface or in the hole of the metal anchor net. The layer thickness is generally 5-10mm, which plays a role in protecting the anchor net support system and the closed tunnel surface. Thin layer spraying materials can be divided into two types: polymer reactive type and cement-based non-reactive type. Cement-based thin layer spraying materials have low cost, slow curing speed and brittleness, which is not conducive to the early support and large deformation tunnels for ductility. The polymer thin spray coating material has a fast curing speed and can obtain the required mechanical strength by regulating the molecular chain structure to meet the support needs of different tunnel geological environments.
[0004] Chinese patent CN116376334A discloses a method for preparing early-strength sprayed materials for reinforcement, support and sealing of mine tunnels. The sprayed materials are mixed with two components A and B. Component A is one of acrylic emulsion, silicone-acrylic solution or chloroprene emulsion, and component B is composed of fly ash, inorganic filler and different types of additives. The prepared sprayed materials have high bonding strength and tensile strength. Chinese patent CN115820062A discloses a waterproof, anti-seepage and high-toughness sprayed material and its preparation method and application. The sprayed materials are mainly composed of cement, silane-modified polyacrylate, titanium dioxide and talcum powder. The silane-modified polyacrylate can react with cement to generate a three-dimensional hydrophobic network structure that gives the sprayed materials flexibility and waterproof and anti-permeability properties. However, this type of sprayed materials still have disadvantages such as poor flame retardancy, low toughness and high cost. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a method for preparing an organic-inorganic composite flame-retardant thin spray material for mining. On the one hand, an acrylate copolymer emulsion with good emulsion stability and narrow particle size distribution is prepared by seed emulsion polymerization method; good flexibility is given by controlling the ratio of soft and hard monomers, and a flame-retardant monomer containing DOPO is introduced in situ to give the copolymer emulsion excellent flame retardant properties. On the other hand, the ester group, carboxyl group, amide group in the acrylate copolymer structure can form a physical / chemical double cross-linked organic-inorganic composite network structure with inorganic materials through multiple hydrogen bonds, coordination bonds, etc., which is conducive to synergistically improving its strength and flame retardant properties.
[0006] The technical problem to be solved by the present invention is achieved through the following technical solutions:
[0007] A method for preparing an organic-inorganic composite flame-retardant thin spray material for mining, characterized in that it comprises the following steps: (1) adding part of the composite emulsifier to deionized water, stirring and dissolving, and then sequentially adding a hard monomer, a soft monomer, a functional monomer, and a flame-retardant monomer, mixing and pre-emulsifying to obtain a pre-emulsion for standby use; (2) sequentially adding NaHCO3 and the remaining composite emulsifier to deionized water, stirring evenly, obtaining a primer for standby use; (3) adding ammonium persulfate to deionized water, stirring evenly, obtaining an ammonium persulfate solution for standby use; (4) taking 15% (volume) of the pre-emulsion obtained in step (1) and adding it to the primer obtained in step (2), and adding one-third (volume) of the pre-emulsion obtained in step (3) The accumulated ammonium persulfate solution is heated to 80°C for seed emulsion polymerization; (5) when the reaction system of step (4) emits blue light and there is no obvious reflux, the remaining (85% by volume) pre-emulsion prepared in step (1) and the remaining two-thirds of the ammonium persulfate solution in step (3) are added dropwise, and the addition of the pre-emulsion is controlled to be completed before the addition of the ammonium persulfate solution. The reaction temperature is raised to 85°C and kept warm for 1 hour; (6) the temperature is cooled to room temperature under stirring, the pH is adjusted to 7-8 with ammonia water, and the emulsion is filtered through a filter to obtain an acrylate copolymer emulsion; (7) calcium formate, cement and fly ash are added to the copolymer emulsion obtained in step (6), and the mixture is stirred and mixed to obtain an organic-inorganic composite thin spraying material for mining.
[0008] Furthermore, the partial composite emulsifier described in step (1) accounts for 2 / 3-1 / 2 of the total mass.
[0009] Furthermore, the composite emulsifier described in step (1) is a mixture of anionic surfactant and nonionic surfactant, the mass ratio of the two is 2:1, and the concentration is 15g / L.
[0010] Furthermore, the composite emulsifier described in step (1) is two of SDBS (sodium dodecylbenzene sulfonate), OP-10 (octylphenol polyoxyethylene ether), and NP-10 (nonylphenol polyoxyethylene ether).
[0011] Furthermore, the hard monomer in step (1) is a mixture of methyl methacrylate at a concentration of 200-250 g / L and styrene at a concentration of 0-100 g / L.
[0012] Furthermore, the soft monomer in step (1) is one of butyl acrylate, decyl acrylate, octyl acrylate, lauryl acrylate and octadecyl acrylate, and the concentration is 150-200 g / L.
[0013] Furthermore, the functional monomer in step (1) is a mixture of one of acrylic acid, methacrylic acid, itaconic acid and fumaric acid at a concentration of 5-10 g / L and acrylamide at a concentration of 5-20 g / L.
[0014] Furthermore, the flame retardant monomer in step (1) is vinyl DOPO, and the concentration is 25-40 g / L.
[0015] Furthermore, the hard monomer, soft monomer, functional monomer and flame retardant monomer described in step (1) are proportioned in parts by weight as follows: 40-50 parts of methyl methacrylate; 10-20 parts of styrene; 30-40 parts of soft monomer; 2-5 parts of functional monomer; and 5-8 parts of flame retardant monomer.
[0016] Furthermore, the mass ratio of the composite emulsifier described in step (1) to all monomers is 2:100-3:100.
[0017] Furthermore, the concentration of NaHCO3 in step (2) is 5-10 g / L.
[0018] Furthermore, the concentration of the ammonium persulfate in step (3) is 0.5-2.5 g / L.
[0019] Furthermore, the mass of the ammonium persulfate in step (3) is 0.2 wt%-1 wt% of the mass of all monomers.
[0020] Furthermore, in step (5), the ratio of the drop rate of the pre-emulsion to that of the ammonium persulfate is 5:1.
[0021] Furthermore, the ratio (in parts by weight) of calcium formate, cement, fly ash and copolymer emulsion in step (7) is as follows: 3-5 parts of calcium formate; 20-30 parts of cement; 25-35 parts of fly ash; and 40-50 parts of copolymer emulsion.
[0022] The advantages of the present invention are as follows: (1) the present invention adopts a seed emulsion polymerization method to introduce different types of monomers to regulate the molecular structure of the copolymer, thereby giving the polymer emulsion excellent mechanical properties, flame retardant properties and compatibility with inorganic fillers; (2) the present invention adopts a reactive phosphorus-based flame retardant monomer, which can introduce an organic flame retardant component into the molecular skeleton of the copolymer, and at the same time utilizes coordination bonds, multiple hydrogen bonds and other interactions with inorganic components such as cement and fly ash to form an organic-inorganic flame retardant system with a three-dimensional network structure, thereby obtaining excellent flame retardant and mechanical properties; (3) the emulsion polymerization method adopted by the present invention has a simple synthesis process and is green and environmentally friendly. The use of fly ash can effectively reduce costs and has broad market application prospects.
[0023] The technical solution of the present invention is described in detail below with reference to the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is the structural formula of the vinyl DOPO flame retardant monomer used in the present invention;
[0025] Figure 2 This is a transmission electron microscope photo of the copolymer emulsion of Example 1 of the present invention;
[0026] Figure 3 It is the infrared spectrum of the copolymer emulsion of the present invention. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below through specific examples, but it should not be understood that the protection scope of the present invention is limited to the following examples.
[0028] Example 1
[0029] A method for preparing an organic-inorganic composite flame-retardant thin spray material for mining, comprising the following steps:
[0030] (1) Take 2 / 3 (by mass) of the composite emulsifier (1.33 g SDBS and 0.67 g OP-10) and add it to a round-bottom flask containing 100 mL of deionized water. After stirring and dissolving, slowly add 50 g methyl methacrylate, 10 g styrene, 30 g butyl acrylate, 1.5 g acrylic acid and 3.5 g acrylamide, and 5 g vinyl DOPO in sequence, mix and pre-emulsify to obtain a pre-emulsion for later use;
[0031] (2) Add 1 g NaHCO3 and the remaining 1 / 3 of the composite emulsifier (0.67 g SDBS and 0.33 g OP-10) to 85 mL of deionized water and stir evenly to obtain a primer for later use;
[0032] (3) Temperature initiation: 15% (volume) of the pre-emulsion obtained in step (1) is added to the primer obtained in step (2), 1 / 3 of ammonium persulfate solution (1 g APS is dissolved in 15 mL water, 5 mL is taken), and the temperature is raised to 80° C. to carry out seed emulsion polymerization;
[0033] (4) When the reaction system of step (3) emits blue light and has no obvious reflux, the remaining pre-emulsion (85% by volume) prepared in step (1) and the remaining 2 / 3 of the ammonium persulfate solution are added dropwise at the same time (the dropping rate of the pre-emulsion and the initiator is controlled at 5:1, and the pre-emulsion is added before the initiator), and the temperature of the reaction system is raised to 85° C. and kept warm for 1 hour;
[0034] (5) cooling to room temperature under stirring, adjusting the pH to 7-8 with aqueous ammonia, and filtering the emulsion with a filter to obtain an acrylate copolymer emulsion;
[0035] (6) Take 80 g of the copolymer emulsion obtained in step (5), add 10 g of calcium formate, 40 g of cement, and 70 g of fly ash, and stir to obtain an organic-inorganic composite thin spraying material for mining.
[0036] Example 2
[0037] A method for preparing an organic-inorganic composite flame-retardant thin spray material for mining, which is different from Example 1 in that 2 / 3 of the composite emulsifier (1.33g SDBS and 0.67g OP-10) is changed to 1 / 2 of the composite emulsifier (1.0g sodium dodecylbenzene sulfonate and 0.5g OP-10), 50g methyl methacrylate, 10g styrene, 30g butyl acrylate, 1.5g acrylic acid and 3.5g acrylamide, 5g vinyl DOPO is changed to 40g methyl methacrylate, 20g styrene, 30g octyl acrylate, 1g methacrylic acid and 1g acrylamide, 8g vinyl DOPO, 1g NaHCO3, the remaining 1 / 3 of the composite emulsifier (0.67g SDBS and 0.33g OP-10) is changed to 2g NaHCO3, the remaining 1 / 2 of the composite emulsifier (1.0g sodium dodecylbenzene sulfonate and 0.5g NP-10), adding 1 / 3 of ammonium persulfate solution (dissolve 1g APS in 15mL water, take 5mL) becomes adding 1 / 3 of ammonium persulfate solution (dissolve 0.2g APS in 15mL water, take 5mL); 80g of copolymer emulsion, adding 10g of calcium formate, 40g of cement, 70g of fly ash becomes 100g of copolymer emulsion, adding 10g of calcium formate, 40g of cement, and 50g of fly ash.
[0038] Example 3
[0039] A method for preparing an organic-inorganic composite flame-retardant thin spray material for mining, which is different from Example 1 in that 2 / 3 of the composite emulsifier (1.33g SDBS and 0.67g OP-10) is changed to 1 / 2 of the composite emulsifier (0.89g SDBS and 0.44g OP-10), 50g methyl methacrylate, 10g styrene, 30g butyl acrylate, 1.5g acrylic acid and 3.5g acrylamide, 5g vinyl DOPO is changed to 50g methyl methacrylate, 20g styrene, 20g decyl acrylate, 2g itaconic acid and 2g acrylamide, 6g vinyl DOPO, the remaining 1 / 3 of the composite emulsifier (0.67g SDBS and 0.33g OP-10) is changed to the remaining 1 / 3 of the composite emulsifier (0.45g SDBS and 0.22g OP-10), 1 / 3 of ammonium persulfate solution (1g APS is dissolved in 15mL water, and 5mL is taken) changed to adding 1 / 3 of ammonium persulfate solution (0.5g APS is dissolved in 15mL water, and 5mL is taken); 80g copolymer emulsion, 10g calcium formate, 40g cement, 70g fly ash are added to become 80g copolymer emulsion, 10g calcium formate, 60g cement, 50g fly ash are added.
[0040] Example 4
[0041] A method for preparing an organic-inorganic composite flame-retardant thin spray material for mining, which is different from Example 1 in that 50g methyl methacrylate, 10g styrene, 30g butyl acrylate, 1.5g acrylic acid and 3.5g acrylamide, 5g vinyl DOPO is changed to 50g methyl methacrylate, 0g styrene, 40g propylene lauryl ester, 1g fumaric acid and 2g acrylamide, 7g vinyl DOPO, adding 1 / 3 of ammonium persulfate solution (dissolving 1g APS in 15mL water and taking 5mL) is changed to adding 1 / 3 of ammonium persulfate solution (dissolving 0.5g APS in 15mL water and taking 5mL); 80g copolymer emulsion, adding 10g calcium formate, 40g cement, 70g fly ash is changed to 80g copolymer emulsion, adding 6g calcium formate, 54g cement, and 60g fly ash.
[0042] Example 5
[0043] A method for preparing an organic-inorganic composite flame-retardant thin spray material for mining, which is different from Example 1 in that 50g of methyl methacrylate, 10g of styrene, 30g of butyl acrylate, 1.5g of acrylic acid and 3.5g of acrylamide are changed to 40g of methyl methacrylate, 20g of styrene, 30g of octadecyl acrylate, 1g of acrylic acid and 4g of acrylamide, and the addition of 1 / 3 of ammonium persulfate solution (1g of APS is dissolved in 15mL of water and 5mL is taken) is changed to the addition of 1 / 3 of ammonium persulfate solution (0.7g of APS is dissolved in 15mL of water and 5mL is taken); 80g of copolymer emulsion, 10g of calcium formate, 40g of cement, and 70g of fly ash are added to 80g of copolymer emulsion, 8g of calcium formate, 60g of cement, and 52g of fly ash are added.
[0044] The performance parameters of the composite thin spray prepared in Examples 1-5 are shown in Table 1
[0045] Table 1
[0046] Material Bond strength (MPa) Compressive strength(MPa) Flame retardant grade Example 1 3.26 4.22 V0 Example 2 3.37 4.82 V0 Example 3 2.88 3.93 V0 Example 4 3.34 3.56 V0 Example 5 3.25 4.66 V0
[0047] Figure 2 This is a transmission electron microscope photograph of the copolymer emulsion of Example 1 of the present invention. It can be seen that the polymer molecular chain of the prepared copolymer emulsion presents a cross-linked nano-network structure, which is conducive to compounding with inorganic fillers.
[0048] Figure 3 The infrared spectra of the copolymer emulsions of Examples 1-5 of the present invention show the stretching vibration peak of C=O (1730 cm -1 ), characteristic absorption peak of amide group (1616cm -1 ), COC stretching vibration peaks (1143, 1253 cm -1 ), etc. The presence of these oxygen-containing groups is conducive to forming a physical / chemical double-crosslinked three-dimensional network structure with inorganic fillers through multiple hydrogen bonds and coordination bonds.
[0049] The above embodiments describe the technical solutions of the present invention in detail. Obviously, the present invention is not limited to the described embodiments. Based on the embodiments of the present invention, people familiar with the technical field can also make various changes accordingly, but any changes that are equivalent or similar to the present invention belong to the scope of protection of the present invention.
Claims
1. A method for preparing an organic-inorganic composite flame-retardant thin spray material for mining, characterized in that: The steps include: (1) adding part of the composite emulsifier to deionized water, stirring to dissolve, and then sequentially adding hard monomer, soft monomer, functional monomer, and flame retardant monomer, mixing and pre-emulsifying to obtain a pre-emulsion for standby use; the composite emulsifier is a mixed solution of anionic surfactant and nonionic surfactant, the mass ratio of the two is 2:1, and the concentration is 15g / L; the part of the composite emulsifier is 2 / 3-1 / 2 of the total mass; the mass ratio of the composite emulsifier to all monomers is 2:100-3:100; (2) adding NaHCO3 and the remaining composite emulsifier to deionized water in sequence, stirring evenly, to obtain a primer solution for standby use; the concentration of the NaHCO3 is 5-10 g / L; (3) adding ammonium persulfate into deionized water and stirring evenly to obtain an ammonium persulfate solution for standby use; the concentration of the ammonium persulfate is 0.5-2.5 g / L; (4) taking 15% (volume) of the pre-emulsion obtained in step (1) and adding it to the primer obtained in step (2), adding one-third of the volume of the ammonium persulfate solution obtained in step (3), and heating the mixture to 80° C. to carry out a seed emulsion polymerization reaction; (5) When the reaction system of step (4) emits blue light and has no obvious reflux, the remaining 85% (volume) pre-emulsion prepared in step (1) and the remaining two-thirds of the ammonium persulfate solution in step (3) are added dropwise, and the addition of the pre-emulsion is controlled to be completed before the addition of the ammonium persulfate solution. The reaction temperature is raised to 85° C. and kept warm for 1 hour; (6) cooling to room temperature under stirring, adjusting the pH to 7-8 with aqueous ammonia, and filtering the emulsion with a filter to obtain an acrylate copolymer emulsion; (7) Add calcium formate, cement and fly ash to the copolymer emulsion obtained in step (6), stir and mix to obtain an organic-inorganic composite thin spraying material for mining.
2. The preparation method according to claim 1, characterized in that: The composite emulsifier described in step (1) is two of SDBS (sodium dodecylbenzene sulfonate), OP-10 (octylphenol polyoxyethylene ether), and NP-10 (nonylphenol polyoxyethylene ether).
3. The preparation method according to claim 1, characterized in that: The hard monomer described in step (1) is a mixture of methyl methacrylate with a concentration of 200-250 g / L and styrene with a concentration of 0-100 g / L.
4. The preparation method according to claim 1, characterized in that: The soft monomer described in step (1) is one of butyl acrylate, decyl acrylate, octyl acrylate, lauryl acrylate and octadecyl acrylate, and the concentration is 150-200 g / L.
5. The preparation method according to claim 1, characterized in that: The functional monomer described in step (1) is a mixture of one of acrylic acid, methacrylic acid, itaconic acid and fumaric acid at a concentration of 5-10 g / L and acrylamide (at a concentration of 5-20 g / L).
6. The preparation method according to claim 1, characterized in that: The flame retardant monomer described in step (1) is vinyl DOPO, and the concentration is 25-40 g / L.
7. The preparation method according to claim 1, characterized in that: The hard monomer, soft monomer, functional monomer and flame retardant monomer described in step (1) are proportioned by weight as follows: Methyl methacrylate 40-50; Styrene 10-20; Soft monomer 30-40; Functional monomers 2-5; Flame retardant monomer 5-8.
8. The preparation method according to claim 1, characterized in that: The mass of the ammonium persulfate described in step (3) is 0.2wt%-1wt% of the mass of all monomers.
9. The preparation method according to claim 1, characterized in that: The ratio of the drop rate of the pre-emulsion to that of ammonium persulfate in step (5) is 5:
1.
10. The preparation method according to claim 1, characterized in that: The proportions (by weight) of calcium formate, cement, fly ash and copolymer emulsion described in step (7) are as follows: Calcium formate 3-5; Cement 20-30; Fly ash 25-35; Copolymer emulsion 40-50; Fly ash 25-35; Copolymer emulsion 40-50.
Citation Information
Patent Citations
Waterproof anti-permeability high-toughness thin spraying material as well as preparation method and application thereof
CN115820062A
Preparation method of flexible early-strength thin spraying material for reinforcing, supporting and sealing mine roadway
CN116376334A